Safety and security of chemical industrial plants - Maravić, Mirna; Perera, Rohan; Črnko, Marina (Crisis Management Days, 2024)
Industry is the driving force of the economy with which the progress is being made. It plays an important role in the global economy. Rising development of chemical industry is particulary important. In 2022, the total revenue of the chemical industry worldwide was about 5.72 trillion US dollars. The same year, the income of the chemical industry reached the highest value in the last 15 years. The chemical industry converts raw materials (fossil fuels, minerals, metals and water) into various products. Nowadays, it can be considered indispensable. Chemical products are all around us. They can be categorised into the following categories: basic chemicals, pharmaceuticals, specialty chemicals, agricultural chemicals and consumer products. Chemical production and consumption contribute significantly to global employment, trade and economic growth. On the other hand, the impacts of the chemical industry to the environment and human health must also be taken into account. Governments around the world have established guidelines or legislation to determine how to manage the transport, storage, handling, use, consumption and safety of chemicals. International organizations, through conventions and institutions, strive to warn and encourage better and more efficient management of the growing amount of chemicals, and thus of chemical factories. Choosing a suitable site for construction and standards for construction of basic facilities greatly contributes to chemical safety. A major risk in the operation of the plant itself is the human factor. This article will give an overview of risks and challenges chemical industry safety is presented with. Key words: economy, safety, security, chemical Introduction With this article, we will continue to work on the topic that started last year on chemical safety, and we have expanded to the safety of chemical plants. We will present a picture of the processing industry (chemical industry) in the world and the Republic of Croatia. Data from professional scientific literature, articles and papers available on the Internet, various tables and graphs were used, which in the statistical database gave an accurate and detailed description of the industry and its development both in the world and in the Republic of Croatia. We will focus on safety in the chemical industry as well as the importance of the international organization OPCW. Industry is an important factor in the development of humanity, it is known how much it affects people's lives, either directly or indirectly. People are aware that everything around them is "chemistry", all those material things that surround them are largely the work of industry, especially the chemical industry. We must not forget that a large number of people work in the chemical industry, and this means the development and importance of it, and the concept of safety rises to a higher level. The chemical industry in Croatia and the world will be compared, as it has developed throughout history, as it is today. Today's world is digitized, and the ICT industry plays a key role through transformation through digitization and the development of technological solutions, but could it do without the chemical industry?! The international organization (Organization for the Prohibition of Chemical Weapons (OPCW), as well as the European Union (European Chemical Agency (ECHA) - by the REACH Regulation (Registration, Evaluation, Authorization and restriction of Chemicals), Classification, Labeling and Packaging (CLP), Regulation on Biocidal Products (BPR), Regulation on Prior Informed Consent (PIC), etc., by introducing applicable legislation, they ensure the safety of the worker himself, as well as the people who are in the vicinity of the industrial plant It is important to emphasize the cooperation between all stakeholders in the chemical production process, (international communities, universities, academic communities, etc.). chemical industry, but also safety in its plant. Work methodology The methodology of the work explains the subject and goal of the text, shows the structure of the text, the methods and sources used to create this text. Some of the sources that will be used in the work are mostly internet sources: scientific articles, scientific papers, newspaper articles and, to a lesser extent, books. All sources will enable a detailed analysis of the work. We will also use statistical data from the State Statistical Office of the Republic of Croatia, as well as data from "Statista", a global platform for data and business intelligence with an extensive collection of statistics, founded in Germany. A good infrastructure is essential for the safety and security of chemical plants, and therefore development, which is why it is important to invest in new technologies, which ensure the safety of workers and the environment. Human been is the key in industrial plants and every mistake he makes is a risk for everything else. Through seminars, the OPCW points out the dangers lurking in chemical plants and tries to warn people about the existence of dangers through seminars and articles. Danger also lurks through cyberattacks on chemical plants, which can lead to major unwanted consequences. Results We will point out that we cannot do without chemical products, and no one would chemical factories, or to put it that way, it is necessary to take risk factors into account when dealing with such an important plant. It is necessary to include all stakeholders in the entire process, including those outside the plant. It is necessary to create a legislative system that works and enables the best and most efficient production possible. Develop technologies and create new innovations and ideas to prevent accidents. It is necessary to include the ICT sector in chemical plants and in cooperation with them to enable plant safety.